Resilience State Security and the Role Sedative Agents in Military Pharmacy for State Defense in Future War - Gilang Bhakti Nusantara; Syahrul Tuba (Budapest International Research and Critics University, 2022)
National defense is closely related to the role of an intelligence officer who is strong and capable of safeguarding the country's sovereignty. Intelligence covers many fields. One of those is medical intelligence. Mitragynine can be used as a sedative agent in a medical intelligence operation. To analyze a sedative agent in intelligent medical purposing of military aspect. This paper determines the role of Military Pharmacy in medical intelligence to support national defense using natural substances that contain a sedative agent. This research used narrative review method for this study obtained from Crossref, google scholar, PubMed, and Scopus range 2010 to 2021 in the English language, using the following terms: